Genomics and transcriptomics-guided metabolic engineering Corynebacterium glutamicum for l-arginine production. (November 2022) - Zhao, Zhenqiang; Cai, Mengmeng; Liu, Yunran; Hu, Mengkai; Yang, Fengyu; Zhu, Rongshuai; Xu, Meijuan; Rao, Zhiming
Graphical abstract: Highlights: Random mutagenesis and screening were applied to obtain the target strains. Revealing genetic and global metabolic differences by multi-omics analysis. Balancing metabolic fluxes through systemic metabolic engineering. Overexpression of a cofactor regeneration system from Escherichia coli. Developing a matched fermentation process improved l -arginine production. Abstract: l -arginine is a semi-essential amino acid that is broadly used as food additives and pharmaceutical intermediates. The synthesis of l -arginine is restricted by complex metabolic mechanisms and suboptimal fermentation conditions. Initially, a mutant strain that accumulated 19.4 g/L l -arginine was generated by random mutagenesis. Subsequently, a mutation of the repressor protein (argR G159D ) in the l -arginine operon and glutamate synthase ( gltD ) with 532-fold upregulation were identified to be vital for l -arginine production by multi-omic analysis. Systematic metabolic engineering was used to modify the strain, which included interfering with α-ketoglutarate dehydrogenase complex (ODHC) activity by knocking out serine/threonine-protein kinase ( pknG ), enhancing the expression of multiple key enzymes in the l -arginine synthesis pathway, and increasing the availability of intracellular cofactor (NADPH) and energy (ATP). Finally, C. glutamicum ARG12 produced 71.3 g/L l -arginine, with a yield of 0.43 g/g glucose by fermentation optimization. This study provides new ideas to boost l -arginine production.